2007
DOI: 10.1007/s00392-007-0546-4
|View full text |Cite
|
Sign up to set email alerts
|

Early and mid-term outcome of the arterial switch operation in 114 consecutive patients

Abstract: The ASO can be performed safely and with low mortality and morbidity even in patients with complex TGA. Follow-up of these patients is required to detect residual problems like supravalvular pulmonary stenosis, coronary problems, arrhythmias and aortic valve dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
1
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 24 publications
1
18
1
2
Order By: Relevance
“…Our patients had excellent operative results with mortality less than 1 % which compares favorably to other reports [12,13]. Despite the excellent mortality outcomes, a subgroup of patients had a protracted postoperative length of stay.…”
Section: Commentsupporting
confidence: 51%
See 1 more Smart Citation
“…Our patients had excellent operative results with mortality less than 1 % which compares favorably to other reports [12,13]. Despite the excellent mortality outcomes, a subgroup of patients had a protracted postoperative length of stay.…”
Section: Commentsupporting
confidence: 51%
“…First, we did not describe postoperative residual anatomical lesions, low cardiac output state, and other postoperative factors that might have affected length of stay. Several reports have been published exploring these associations [3,9,[11][12][13]. Furthermore, the cardiopulmonary bypass time was statistically longer in the LL stay group.…”
Section: Commentmentioning
confidence: 86%
“…Survival rates for corrective and for complex palliative cardiac surgery procedures in neonates have significantly improved over the last 10 years [1][2][3][4]. The incidence of low weight for gestational age in newborns affected with congenital heart defects has been reported to be significantly higher when compared with the normal newborn population [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…The known risk factors for the mortality and morbidity for ASO in complete TGA were combined with anatomical defects, unusual coronary artery anatomy, prolonged CPB time, preterm birth and low body weight at the time of the operation8,10,15,16). Although the presence of a VSD or aortic arch obstruction in complete TGA has been described as a significant risk factor10,17), we showed favorable outcome in spite of different types of TGA anatomy.…”
Section: Discussionmentioning
confidence: 56%
“…Due to the immaturity of organ systems, these patients are exposed to a specific risk resulting from noxious effects of extracorporeal circulation, especially on the central nervous system23,24). Prandstetter et al16) reported that the body weight, less than 2.5 kg at the time of the operation, was the only risk factor for increased hospital mortality. As surgical reasons for the adverse outcome of patients could not be identified, they concluded that immaturity of organ systems is the main reason for the increased risk of mortality and morbidity in this group.…”
Section: Discussionmentioning
confidence: 99%